Preparation method of perovskite-polymer film and perovskite solar cell
By introducing unsaturated monomers as additives to perovskite solar cells, the perovskite-polymer film is prepared, which solves the problem of rapid degradation of perovskite solar cell devices under the influence of moisture, and significantly improves the performance and stability of the device.
Patent Information
- Application Number
- CN202411661054.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-20
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2044-11-20
AI Technical Summary
Perovskite solar cell devices are susceptible to rapid degradation caused by moisture in the external environment, resulting in rapid decline in performance, limiting their commercialization.
Unsaturated monomers are used as additives, and a mixture of ABX3 perovskite precursor solution and a low-boiling point unsaturated monomer and initiator are prepared. Perovskite-polymer films are prepared after stirring, filtration and annealing to improve the performance and stability of perovskite solar cells.
Through the introduction of unsaturated monomers, the perovskite crystal quality is improved, and the polymers generated by in-situ polymerization enhance the stability of the film, improving the performance and humidity stability of perovskite solar cell devices.
Smart Images

Figure CN119677372A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of solar cells, and in particular to a method for preparing a perovskite-polymer film and a perovskite solar cell. Background Art
[0002] With the development of human life and production, the demand for energy is increasing. At present, the main consumption is still traditional fossil energy. However, in the process of consuming a large amount of traditional fossil energy, it is inevitable that a lot of pollution will be caused to the environment, so it is urgent to develop a new clean energy to meet the growing needs of mankind. As a clean energy with huge energy, solar energy has been paid attention to and utilized by people. At present, silicon-based solar cell devices have been commercialized, but they are also accompanied by many shortcomings, and a new material is needed to make up for these shortcomings. As a new optoelectronic material, perovskite has developed rapidly in this context. Because it has many advantages, such as adjustable band gap, long carrier diffusion length, light weight and simple preparation method, it is highly favored. In the past decade of development, the photoelectric conversion efficiency of perovskite solar cells has been rapidly improved, from the initial 3.8% to the current more than 26%, and the conversion efficiency is comparable to that of commercial silicon-based solar cells. In the process of rapid development of the performance of perovskite solar cells, its stability is also a major obstacle to its commercialization.
[0003] Since perovskite is an ionic crystal, the interaction between various components is much smaller than covalent bonds, so it is very easy to be affected by the external environment and cause degradation. For example, water in the environment will induce the rapid degradation of perovskite crystals, resulting in rapid decline in device performance. At present, researchers have used many methods to overcome this problem, such as isolating the device from the environment through later packaging to reduce the impact of moisture in the environment on the device. Or introduce additives into perovskite to increase the stability of perovskite. Summary of the invention
[0004] One of the purposes of the present invention is to provide a method for preparing a perovskite-polymer film, using an unsaturated monomer as an additive introduced into the perovskite to improve the performance of the perovskite solar cell device and enhance its stability.
[0005] A second object of the present invention is to provide a perovskite solar cell with superior device performance and strong stability.
[0006] The solution adopted by the present invention to achieve one of the purposes is: a method for preparing a perovskite-polymer film, comprising the following steps:
[0007] (1) preparing ABX3 type perovskite precursor solution;
[0008] (2) preparing a mixed solution of a low-boiling point unsaturated monomer and an initiator; adding the mixed solution to the precursor solution prepared in step (1), and stirring until the reaction is complete;
[0009] (3) filtering the solution after the reaction in step (2) is completed and coating it on the surface of the substrate, and obtaining the perovskite-polymer film after annealing.
[0010] Preferably, in step (1), the unsaturated monomer is at least one of ethyl acrylate (EA), methyl acrylate, phenylethyl acrylate (PEA), n-propyl acrylate, and isopropyl acrylate.
[0011] Preferably, in step (1), the initiator is at least one of azobisisobutyronitrile (AIBN), benzoyl peroxide (BPO), and azobisisoheptanenitrile (ABVN).
[0012] Preferably, in step (1), the content of the initiator relative to the unsaturated monomer is 0.1 wt%-1.5 wt%.
[0013] Preferably, in step (1), the content of the initiator relative to the unsaturated monomer is 0.5 wt %.
[0014] Preferably, in step (2), the amount of the mixed solution added is 0.1-30 μl / ml.
[0015] Preferably, in step (2), the A-position cation in the ABX3-type perovskite is a formamidinium ion FA + , Cesium ion Cs + and methylamine ion MA + wherein the formamidinium ion FA + The molar percentage of cations in the A position is 79%-95%, and the cesium ion Cs + The molar percentage of the total A-site cations is 0-10%, and the methylamine ion MA + The molar percentage of the total A-site cations is 0-16%.
[0016] Preferably, in step (2), X in the ABX3 type perovskite is Br - and I - , where Br - The molar percentage of the content of X is 0-40%, and the remainder is I - , the B-site ion is lead ion Pb 2+ .
[0017] Preferably, in step (2), the ABX3 perovskite precursor solution is prepared by a solution method, and the solvent used is a mixture of dimethyl sulfoxide and N,N-dimethylformamide in a volume ratio of 1:4; the concentration of the perovskite component in the perovskite precursor solution is 1M-1.6M.
[0018] Preferably, in step (3), the annealing temperature is 100°C.
[0019] The solution adopted by the present invention to achieve the second purpose is: a perovskite solar cell, including a perovskite-polymer film prepared by the preparation method.
[0020] At present, the additives used to regulate the crystallization of perovskites include two categories: small molecule additives and polymer additives. Small molecule additives are easy to dissolve, and there are more choices for dissolving small molecules. At the same time, small molecules are easier to diffuse in the solution, so that the interaction with the perovskite component is less affected by the steric hindrance of the molecules. However, due to the relatively small molecular weight, the stability of small molecules will be weaker. Polymer additives have a much stronger stability due to their large molecular weight, but due to the large molecular weight of polymers, it is more difficult to dissolve, and some specific solvents are required to dissolve, and the solubility will be correspondingly lower. On the other hand, the functional groups of polymers have greater steric hindrance due to the influence of the main chain, and the interaction between them and the perovskite components in the solution is more restricted. This makes the addition of polymers as additives to perovskite solutions more restricted than small molecule additives.
[0021] The interaction between the unsaturated monomer and the perovskite component improves the crystallization quality of the perovskite. At the same time, during the crystallization annealing process, the unsaturated monomer undergoes in-situ polymerization in the presence of an initiator, and the resulting polymer exists in the perovskite film and the upper and lower interfaces. With the improved crystallization quality of the perovskite film and the passivation effect of the polymer, the performance of the perovskite solar cell device is improved. On the other hand, due to the hydrophobicity of the polymer, the effect of water in the air on the perovskite film is slowed down, enhancing the humidity stability of the perovskite solar cell device.
[0022] In the present invention, the unsaturated monomer selected has a low boiling point, which is lower than the annealing temperature. The temperature of the perovskite crystallization annealing is sufficient to completely volatilize the unpolymerized monomer and avoid monomer residues. After annealing, only polymers remain in the perovskite film, which produces passivation and hydrophobic effects. The present invention can be used to improve the performance of perovskite solar cell devices and enhance the stability of the devices.
[0023] The present invention has the following advantages and beneficial effects:
[0024] In the present invention, unsaturated monomers are used as additives. Before polymerization, they have the characteristics of small molecules and are easy to dissolve. At the same time, small molecules are also easier to diffuse in the solution, so that the interaction with the perovskite component is less affected by the steric hindrance of the molecules. However, in the process of perovskite crystallization, the unsaturated monomers are converted into polymers through in-situ polymerization. They have the stable characteristics of polymers, and the hydrophobicity also increases the stability of perovskite to water molecules in the air. Therefore, the unsaturated monomer additive has the characteristics of small molecules and polymers at the same time, and while improving the performance of the perovskite solar cell device, the stability of the device is enhanced. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 is the performance diagram of adding different contents of unsaturated monomer additive EA to perovskite, where Figure 1 a is the change of the open circuit voltage (Voc) of the device with the EA content, Figure 1 b is the variation of the short-circuit current (Jsc) of the device with the EA content, Figure 1 c is the change of filling factor (FF) with EA content, Figure 1 d is the change of photoelectric conversion efficiency (PCE) with EA content;
[0026] Figure 2 This is the performance diagram of adding different amounts of initiator AIBN to perovskite, where Figure 2 a is the change of Voc of the device with AIBN content, Figure 2 b is the change of Jsc of the device with EA content, Figure 2 c is the change of FF with AIBN content, Figure 2 d is the change of PCE with AIBN content;
[0027] Figure 3 This is the performance diagram of adding different contents of unsaturated monomer additive PEA to perovskite, where Figure 3 a is the change of Voc of the device with PEA content, Figure 3 b is the change of Jsc of the device with PEA content, Figure 3 c is the change of FF with PEA content, Figure 3 d is the change of PCE with PEA content;
[0028] Figure 4 The following are the actual pictures of the perovskite films with different contents of EA and AIBN added before and after aging in an environment with a humidity of 85%;
[0029] Figure 5 The UV-Vis spectra of the perovskite film with different contents of EA and AIBN aged in an environment with a humidity of 85%. Figure 5a is the UV-Vis spectrum of the perovskite film of the sample control in an environment with a humidity of 85% over time. Figure 5 b is the UV-Vis spectrum of the perovskite film of sample AIBN-0 changing with time in an environment with a humidity of 85%. Figure 5 c is the UV-Vis spectrum of the perovskite film of sample EA-5 changing with time in an environment with a humidity of 85%. Figure 5 d is the UV-Vis spectrum of the perovskite film of sample EA-30 changing with time in an environment with a humidity of 85%;
[0030] Figure 6 It is the maximum power point output (MPP) curve of the unpackaged device in the environment. DETAILED DESCRIPTION
[0031] For a better understanding of the present invention, the following examples are provided to further illustrate the present invention, but the present invention is not limited to the following examples.
[0032] Example 1
[0033] A pin structured perovskite solar device, the structure of which is FTO / NiO / Me-4PACz / perovskite layer / C 60 / BCP / Cu, wherein the perovskite layer is prepared by preparing the components of FA 0.9 MA 0.06 Cs 0.04 The perovskite solution with a PbI3 concentration of 1.45M and a mixed solvent of DMSO and DMF (volume ratio DMSO:DMF=1:4) was stirred overnight in a glove box. Before filtering, a mixed solution of EA and AIBN was prepared (the content of AIBN relative to EA was 0.5wt%), and then 5μl of the mixed solution of EA and AIBN was added to 1ml of the perovskite solution and stirred. After half an hour, the solution was filtered and spin-coated, and then annealed at 100°C for 1h to obtain a sample named EA-5, whose performance diagram is as follows Figure 1 The average photoelectric conversion efficiency (PCE) of the device is 25.14%, which is an improvement over the control device. In the air environment aging with a relative humidity of 85%, the UV-vis spectrum of the perovskite can be seen ( Figure 5 ), the absorption of the perovskite film slightly decreases with the change of aging time, indicating that the film has slightly degraded in this humidity environment. When the unpackaged device is placed in an air environment for maximum power point output (MPP) ( Figure 6 ), relative humidity of 55%-60%, temperature of about 45°C, it can be found that the photoelectric conversion performance of the EA-5 device has dropped to 90% of the initial performance after about 256h of aging (T 90). Compared with the control device, the decline is slower and the stability is enhanced.
[0034] Example 2
[0035] Pin structure perovskite solar device, the structure of which is FTO / NiO / Me-4PACz / perovskite layer / C 60 / BCP / Cu, the perovskite layer is prepared by preparing the components of FA 0.9 MA 0.06 Cs 0.04 The perovskite solution with a PbI3 concentration of 1.45M and a mixed solvent of DMSO and DMF (volume ratio DMSO:DMF=1:4) was stirred overnight in a glove box. Before filtering, a mixed solution of EA and AIBN was prepared (the content of AIBN relative to EA was 0.5wt%), and then 30μl of the mixed solution of EA and AIBN was added to 1ml of the perovskite solution and stirred. After half an hour, the solution was filtered and spin-coated, and then annealed at 100℃ for 1h to obtain a sample named EA-30, whose performance diagram is as follows Figure 1 The average photoelectric conversion efficiency (PCE) of the device is 22.78%. Figure 4 It can be found that in an air environment with a relative humidity of 85%, the film is flat and black before aging. After 48 hours of aging, the edge of the perovskite film is slightly degraded and turns yellow. From the UV-vis spectrum of perovskite, it can be seen that ( Figure 5 ), with the change of aging time, the absorption of the perovskite film has basically not changed, indicating that the degradation rate of the film in this humidity environment is slower than that of the control sample, and the stability of the film has been enhanced.
[0036] Example 3
[0037] Pin structure perovskite solar device, the structure of which is FTO / NiO / Me-4PACz / perovskite layer / C 60 / BCP / Cu, the perovskite layer is prepared by preparing the components of FA 0.9 MA 0.06 Cs 0.04 The perovskite solution with a PbI3 concentration of 1.45M and a mixed solvent of DMSO and DMF (volume ratio DMSO:DMF=1:4) was stirred overnight in a glove box. Before filtering, a mixed solution of EA and AIBN was prepared (the content of AIBN relative to EA was 1.5wt%), and then 5μl of the mixed solution of EA and AIBN was added to 1ml of the perovskite solution and stirred. After half an hour, the solution was filtered and spin-coated, and then annealed at 100°C for 1h to obtain a sample named AIBN-1.5, whose performance diagram is as follows Figure 2The average photoelectric conversion efficiency (PCE) of the device is 24.23%.
[0038] Example 4
[0039] Pin structure perovskite solar device, the structure of which is FTO / NiO / Me-4PACz / perovskite layer / C 60 / BCP / Cu, the perovskite layer is prepared by preparing the components of FA 0.9 MA 0.06 Cs 0.04 The perovskite solution with a PbI3 concentration of 1.45M and a mixed solvent of DMSO and DMF (volume ratio DMSO:DMF=1:4) was stirred overnight in a glove box. Before filtering, a mixed solution of EA and AIBN was prepared (the content of AIBN relative to EA was 0.5wt%), and then 15μl of the mixed solution of EA and AIBN was added to 1ml of the perovskite solution and stirred. After half an hour, the solution was filtered and spin-coated, and then annealed at 100℃ for 1h to obtain a sample named EA-15, whose performance diagram is as follows Figure 1 The average photoelectric conversion efficiency (PCE) of the device is 24.46%.
[0040] Example 5
[0041] Pin structure perovskite solar device, the structure of which is FTO / NiO / Me-4PACz / perovskite layer / C 60 / BCP / Cu, the perovskite layer is prepared by preparing the components of FA 0.9 MA 0.06 Cs 0.04 The perovskite solution with a PbI3 concentration of 1.45M and a mixed solvent of DMSO and DMF (volume ratio DMSO:DMF=1:4) was stirred overnight in a glove box. Before filtering, a mixed solution of EA and AIBN was prepared (the content of AIBN relative to EA was 0.25wt%), and then 5μl of the mixed solution of EA and AIBN was added to 1ml of the perovskite solution and stirred. After half an hour, the solution was filtered and spin-coated, and then annealed at 100°C for 1h to obtain a sample named AIBN-0.25, whose performance diagram is as follows Figure 2 The average photoelectric conversion efficiency (PCE) of the device is 24.88%.
[0042] Example 6
[0043] Pin structure perovskite solar device, the structure of which is FTO / NiO / Me-4PACz / perovskite layer / C 60 / BCP / Cu, the perovskite layer is prepared by preparing the components of FA 0.79 MA 0.15Cs 0.05 PbI 2.7 Br 0.3 The perovskite solution with a concentration of 1.35M, the mixed solvent is DMSO and DMF (volume ratio DMSO:DMF=1:4), and it is stirred overnight in a glove box. Before filtering, first prepare a mixed solution of phenethyl acrylate (PEA) and azobisisoheptanenitrile (ABVN) (the content of ABVN relative to PEA is 0.5wt%), then add 5μl of the mixed solution of PEA and ABVN to 1ml of the perovskite solution and stir. After half an hour, the solution is filtered and spin-coated, and then annealed at 100℃ for 1h to obtain a sample named PEA-5, and its performance diagram is as follows Figure 3 The average photoelectric conversion efficiency (PCE) of the device is 22.9%. Figure 3 It can be found that with the increase of PEA content, the device performance first increases and then decreases, which has the same trend as the change of EA content.
[0044] Comparative Example 1
[0045] Pin structure perovskite solar device, the structure of which is FTO / NiO / Me-4PACz / perovskite layer / C 60 / BCP / Cu, the perovskite layer is prepared by preparing the components of FA 0.9 MA 0.06 Cs 0.04 The perovskite solution with a PbI3 concentration of 1.45M and a mixed solvent of DMSO and DMF (volume ratio DMSO:DMF=1:4) was stirred overnight in a glove box. The solution was filtered and spin-coated, and then annealed at 100°C for 1h. The sample was named control, and its performance graph is as follows Figure 1 The average photoelectric conversion efficiency (PCE) of the device is 23.91%. Figure 4 It can be found that in an air environment with a relative humidity of 85%, the film is flat and black before aging. After 48 hours of aging, the perovskite film is partially degraded and turns yellow. In addition, it can be seen from the aging UV-vis spectrum ( Figure 5 ), the absorption of the perovskite film gradually decreases with the change of aging time, indicating that the film has degraded in this humidity environment. When the unpackaged device is placed in an air environment for maximum power point output (MPP) ( Figure 6 ), relative humidity of 55%-60%, temperature of about 45℃, it can be found that the photoelectric conversion performance of the control device has dropped to 80% of the initial performance after about 75h of aging (T 80 ).
[0046] Comparative Example 2
[0047] Pin structure perovskite solar device, the structure of which is FTO / NiO / Me-4PACz / perovskite layer / C 60 / BCP / Cu, the perovskite layer is prepared by preparing the components of FA 0.9 MA 0.06 Cs 0.04 The perovskite solution with a PbI3 concentration of 1.45M and a mixed solvent of DMSO and DMF (volume ratio DMSO:DMF=1:4) was stirred overnight in a glove box. Before filtering, a mixed solution of EA and AIBN was first prepared (the content of AIBN relative to EA was 0%), and then 5μl of the mixed solution of EA and AIBN was added to 1ml of the perovskite solution and stirred. After half an hour, the solution was filtered and spin-coated, and then annealed at 100°C for 1h to obtain a sample named AIBN-0, whose performance diagram is as follows Figure 2 The average photoelectric conversion efficiency (PCE) of the device is 24.43%. Figure 4 It can be found that in an air environment with a relative humidity of 85%, the film is flat and black before aging. After 48 hours of aging, a small amount of degradation appears at the edge of the perovskite film and turns into yellow. From the UV-vis spectrum of perovskite, it can be seen that ( Figure 5 ), with the change of aging time, the absorption of the perovskite film gradually decreases, but the rate of decrease is slower than that of the control sample, indicating that the degradation rate of the film in this humidity environment is slower than that of the control sample, and the stability of the film is enhanced.
[0048] Comparative Example 3
[0049] Pin structure perovskite solar device, the structure of which is FTO / NiO / Me-4PACz / perovskite layer / C 60 / BCP / Cu, the perovskite layer is prepared by preparing the components of FA 0.79 MA 0.15 Cs 0.05 PbI 2.7 Br 0.3 The perovskite solution with a concentration of 1.35M and a mixed solvent of DMSO and DMF (volume ratio DMSO:DMF=1:4) was stirred overnight in a glove box. The solution was filtered and spin-coated, and then annealed at 100°C for 1h to obtain a sample named PEA-0. Its performance diagram is as follows Figure 3 The average photoelectric conversion efficiency (PCE) of the device is 22.69%.
[0050] The above is only a preferred embodiment of the present invention, which certainly cannot be used to limit the scope of rights of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and changes can be made without departing from the principle of the present invention, and these improvements and changes are also regarded as the protection scope of the present invention.
Claims
1. A method for preparing a perovskite-polymer film, characterized in that: The following steps are involved: (1) preparing ABX3 type perovskite precursor solution; (2) preparing a mixed solution of a low-boiling point unsaturated monomer and an initiator; adding the mixed solution to the precursor solution prepared in step (1), and stirring until the reaction is complete; (3) filtering the solution after the reaction in step (2) is completed and coating it on the surface of the substrate, and obtaining the perovskite-polymer film after annealing.
2. The method for preparing a perovskite-polymer film according to claim 1, characterized in that: In the step (1), the unsaturated monomer is at least one of ethyl acrylate, methyl acrylate, phenylethyl acrylate, n-propyl acrylate, and isopropyl acrylate.
3. The method for preparing a perovskite-polymer film according to claim 1, characterized in that: In the step (1), the initiator is at least one of azobisisobutyronitrile, benzoyl peroxide, and azobisisoheptanenitrile.
4. The method for preparing a perovskite-polymer film according to claim 1, characterized in that: In the step (1), the content of the initiator relative to the unsaturated monomer is 0.1 wt%-1.5 wt%.
5. The method for preparing a perovskite-polymer film according to claim 1, characterized in that: In the step (2), the amount of the mixed solution added is 0.1-30 μl / ml.
6. The method for preparing a perovskite-polymer film according to claim 1, characterized in that: In the step (2), the cation at position A in the ABX3 type perovskite is a formamidinium ion FA + , Cesium ion Cs + and methylamine ion MA + wherein the formamidinium ion FA + The molar percentage of cations in the A position is 79%-95%, and the cesium ion Cs + The molar percentage of the total A-site cations is 0-10%, and the methylamine ion MA + The molar percentage of the total A-site cations is 0-16%.
7. The method for preparing a perovskite-polymer film according to claim 1, characterized in that: In the step (2), X in the ABX3 type perovskite is Br - and I - , where Br - The molar percentage of the content of X is 0-40%, and the remainder is I - , the B-site ion is lead ion Pb 2+ .
8. The method for preparing a perovskite-polymer film according to claim 1, characterized in that: In the step (2), the ABX3 perovskite precursor solution is prepared by a solution method, and the solvent used is a mixture of dimethyl sulfoxide and N,N-dimethylformamide in a volume ratio of 1:4; the concentration of the perovskite component in the perovskite precursor solution is 1M-1.6M.
9. The method for preparing a perovskite-polymer film according to claim 1, characterized in that: In the step (3), the annealing temperature is 100°C.
10. A perovskite solar cell, characterized in that: A perovskite-polymer film prepared by the preparation method according to any one of claims 1 to 9.
Citation Information
Patent Citations
Perovskite thin film, perovskite solar cell and preparation method thereof
CN108922972A
Monomer auto-polymerization assisted synthesized perovskite solar cell and preparation method thereof
CN114284441A
Precursor solution, perovskite thin film, perovskite assembly and preparation method thereof
CN114551722A
Perovskite solar cell and preparation method thereof
CN115249771A
Perovskite-polymer composite material, preparation method and perovskite solar cell
CN115528178A